The Impact of Automation and Artificial Intelligence on Employment in Germany’s Manufacturing Sector - Do, Thi Ngoc Huyen; Mazouch, Petr, 1981-; Lichard, Tomáš; Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky (2025)
This thesis investigates the impact of automation and artificial intelligence (AI) on employment within Germany's manufacturing sector, distinguishing between high-tech and low-tech industries. Drawing on regional panel data from 2012 to 2022, the study employs multiple panel models to evaluate the role of technological advancement, controlling for education, demographics, and export dependence. The findings reveal a dual reality: R&D-driven automation and AI positively influence employment in high-tech manufacturing, underscoring the role of innovation in sustaining employment growth. Conversely, low-tech employment is shaped less by technology and more by workforce education, aging populations, and global trade exposure. These contrasting dynamics highlight the need for targeted, sector-specific policy interventions that foster inclusive labor market outcomes in response to rapid technological change.
Vedoucí práce: Petr Mazouch
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky, 2025
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2025
Způsob přístupu: Internet
Keywords: data analysis and modeling [obor dipl. práce]; diplomové práce; master's theses